1987
DOI: 10.1126/science.238.4827.657
|View full text |Cite
|
Sign up to set email alerts
|

Sea Surface Temperature, Surface Wind Divergence, and Convection over Tropical Oceans

Abstract: Large-scale convection over the warm tropical oceans provides an important portion of the driving energy for the general circulation of the atmosphere. Analysis of regional associations between ocean temperature, surface wind divergence, and convection produced two important results. First, over broad regions of the Indian and Pacific oceans, sea surface temperatures (SSTs) in excess of 27.5 degrees C are required for large-scale deep convection to occur. However, SSTs above that temperature are not a sufficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
413
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 623 publications
(459 citation statements)
references
References 18 publications
33
413
0
Order By: Relevance
“…In the central equatorial Indian Ocean where SST is close to the necessary threshold for atmospheric deep convection [e.g., Graham and Barnett, 1987], small variations or errors in SST estimation can lead to large uncertainties in surface heat exchange. A SST change of 1 K in the DYNAMO mooring data could lead to an air-sea heat flux change of 41 to 48 W m 22 .…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In the central equatorial Indian Ocean where SST is close to the necessary threshold for atmospheric deep convection [e.g., Graham and Barnett, 1987], small variations or errors in SST estimation can lead to large uncertainties in surface heat exchange. A SST change of 1 K in the DYNAMO mooring data could lead to an air-sea heat flux change of 41 to 48 W m 22 .…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Observations show conflicting relationships between sea surface temperature (SST) and deep convection in the tropics. Gadgil et al [1984] and Graham and Barnett [1987] reported that there is a correlation between the SST variation and cloudiness for the colder oceans, but the correlation does not exist when SST is above 27.5øC over the Indian and Pacific Oceans. Ramanathan and Collins [1991] found the top of the atmosphere and at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…A relationship between SST and moist convection (MC) has been pointed out in a large number of studies (e.g., Gadgil et al, 1984;Graham and Barnett, 1987;and Zhang, 1993). Tropical deep convection emerges over SST >_ 28øC.…”
Section: Introductionmentioning
confidence: 99%